The Mediating Role of Cardiorespiratory Fitness in the Association between a Negative Lifestyle and Poor Mental Health in Chilean Schoolchildren - Pedro Delgado-Floody; Felipe Caamaño-Navarrete; Guillermo Barahona-Fuentes; Carlos Arriagada-Hernández; Pablo Valdés-Badilla; Indya Del-Cuerpo; Mauricio Cresp-Barría; Manuel Gómez-López (MDPI AG, 2024)
Background: A negative lifestyle has a reported relationship with psychological problems and deteriorated well-being. However, there is little information regarding the mediating role of cardiorespiratory fitness (CRF) in this relationship. Objectives: The objectives of the present study are twofold: first, to investigate the association between negative lifestyle, physical self-concept (PSC), and depression, and second, to assess the potential mediating role of CRF in this complex relationship. Methods: This cross-sectional study included 612 schoolchildren aged between 9 and 14 years from the Araucanía region (southern Chile). CRF was measured using the Leger test, and lifestyle, depression, and PSC were measured using validated questionnaires. Results: A negative lifestyle reported an inverse association with PSC (p < 0.001) and a positive association with depression levels (p < 0.001). The mediation analysis showed that CRF was positively related to PSC (p < 0.001) and inversely related to depression (p = 0.001); besides, the indirect effect CRF acted as a partial mediator in the association between a negative lifestyle and PSC (indirect effect = −1.15; SE = 0.01; 95% CI, −1.87, −0.55) and depression levels (indirect effect = 0.22; SE = 0.08; 95% CI, 0.08, 0.38). Conclusion: In conclusion, CRF in schoolchildren played a potential mediating role in the association between a negative lifestyle and depression and PSC.